ANALISA PEMILIHAN TRANSPORTASI UMUM MENUJU BANDARA SOEKARNO HATTA DENGAN METODE STATED PREFERENCE - Hardiyanti, Siti; Irfan Rifai, Andri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
Transportation is used to facilitate people to do daily activities, and options of transportation mode have an important role in relation to the types of modes and available infrastructures. This study aims to determine what factors influence options of public transportation modes and find out what transportation modes chosen by people who live near Bekasi to Soekarno Hatta Airport by choosing train or bus. The data used in this study are primary data obtained from survey results in the form of questionnaires with the stated preference method by providing several different scenarios. With the influence of variable cost X1, X2 travel time and X3 headway. Furthermore, the secondary data obtained is calculated using the linear regression method and the differences between the utility of the airport train and the bus are used to calculate the probability of the options. The results of the linear regression obtained by the difference in mode selection utilities that is . The conclusion is that the differences in cost, travel time and headway affects the options of transportation modes. Factors that influence the option of public transportation modes are travel time, where the certainty of arrival time to the airport is very important. And the most preferred transportation mode from Bekasi City to Soekarno Hatta Airport is Bus. Where the probability of using bus is greater than airport train.